Silver nanoparticles from Prosopis glandulosa and their potential application as biocontrol of Acinetobacter calcoaceticus and Bacillus cereus - Ali Abdelmoteleb; Benjamín Valdez-Salas; Carlos Ceceña-Duran; Olivia Tzintzun-Camacho; Federico Gutiérrez-Miceli; Onecimo Grimaldo-Juarez; Daniel González-Mendoza (Chemical Speciation & Bioavailability, 2017)
In the present study the characterization and properties of silver nanoparticles from Prosopis glandulosa leaf extract (AgNPs) were investigated using UV–Vis spectroscopic techniques, energy dispersive X-ray spectrometers (EDS), zeta potential and dynamic light scattering. The UV–Vis spectroscopic analysis showed the absorbance peaked at 487 nm, which indicated the synthesis of silver nanoparticles. The experimental results showed silver nanoparticles had Z-average diameter of 421 nm with higher stability (−200 mV). The EDS analysis also exhibited presentation of silver element. Additionally, the different concentrations of AgNPs (25, 50, 75 and 100 mg/mL) showed antibacterial activity against Acinetobacter calcoaceticus and Bacillus cereus. Finally, AgNPs from leaf extracts of P. glandulosa may be used as an agent of biocontrol of microorganism of importance medical. However, further studies will be needed to fully understand the antimicrobial activity of silver nanoparticles obtain from P. glandulosa.